PENERAPAN METODE REGRESI LINEAR SEDERHANA DALAM MEMPREDIKSI TANDAN BUAH SEGAR MASUK DI PKS DOLOK ILIR - Rizki, Fahrizal; Irawan, Eka; Safii, M. (Jurnal Manajamen Informatika Jayakarta, 2024)
Oil palm is a very important crop in the agricultural sector today. This is because oil palm is the country's largest foreign exchange earner as well as a driver of the people's economy and plays a role in employment. Dolok Ilir Palm Oil Mill is one of the business units of PT Perkebunan Nusantara 4 which is engaged in the palm oil sector. As a plantation that has a palm oil processing plant, PKS Dolok Ilir also processes palm oil from other PTPN IV plantation units. Fresh fruit bunches entering the Dolok Ilir PKS are still difficult to predict. The high number of incoming Fresh Fruit Bunches and limited processing capacity causes some fruits cannot be processed on the same day, this will have an impact on reducing the quality of Fresh Fruit Bunches (FFB) and the quality of Crude Palm Oil (CPO). From these problems, an algorithm is needed to predict incoming Fresh Fruit Bunches (FFB) at the Dolok Ilir PKS.